A Study of the Formation Process of Sustainable Regional Ecosystems: Regional Knowledge Creation Research focusing on the Connections and Movements of People and Entities in the Region - Shintaro KATSURA; Ayano NISHIHARA (AAOS Transactions)
This study applies ecosystem research and knowledge creation theory to examine the process of forming sustainable regional ecosystems. In particular, we will focus on the connections and movements of local people and entities. This will open up a new research field, and by doing so, we aim to make both ecosystem research and knowledge creation theory research contribute to solving social issues and creating social value that the world of the 21st century will face.